2008
DOI: 10.1007/s10464-008-9195-7
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Changes for Family to Family Graduates

Abstract: Family members of people with serious mental illnesses (SMI) need information and support to cope with the considerable stresses they experience. The Family to Family Education Program (FtF) is a structured, peer-led, 12-week information and support self-help class for such individuals. Previous research by Dixon et al. (2004) shows reduced subjective burden and increased empowerment among graduates. The present study sought to understand what processes take place during FtF participation that might lead to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
7
25
0
3
Order By: Relevance
“…Subjective burden decreases were also found in our previous studies (13, 14). This fits with our previous qualitative findings regarding change processes among FTF graduates (16) who described themselves as deriving both immediate and time-lagged benefits from FTF. However, the absence of a control condition during this period prevents us from being sure that the changes observed were indeed owing to FTF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Subjective burden decreases were also found in our previous studies (13, 14). This fits with our previous qualitative findings regarding change processes among FTF graduates (16) who described themselves as deriving both immediate and time-lagged benefits from FTF. However, the absence of a control condition during this period prevents us from being sure that the changes observed were indeed owing to FTF.…”
Section: Discussionsupporting
confidence: 91%
“…The immediate benefits gained by Journey of Hope participants were sustained 6 months after that program ended (11), as were immediate post-FTF benefits to participants in both previous smaller studies (13, 14). In a qualitative study examining the processes through which FTF helped participants (16), some participants reported that FTF benefits were still unfolding 1–3 months after FTF was over. However, these samples were all of modest size.…”
Section: Previous Research On Ftfmentioning
confidence: 99%
“…Family-to-Family is currently available in 46 states, Puerto Rico, Canada, and Mexico, and is the most commonly used model of family education (Dixon et al 2001;Lucksted et al 2008). In 2007, demand for a similar program for family caregivers of children and adolescents with mental illnesses resulted in Family-to-Family's progeny, NAMI Basics.…”
Section: Introductionmentioning
confidence: 99%
“…Chien et al (2008) further reported that the FFS program decreased the family burden while increasing the family functionality and social support. Lucksted, Steward, and Forbes (2008) interviewed with the caregivers who completed the FFS program. The subjects reported that they solved problems more efficiently, their self-confidence increased, they became more understanding toward the patients, they had less anger and stress, and they could cope with stress more effectively after joining the FFS program.…”
Section: Results Obtained From the Ways Of Coping With Stress Scalementioning
confidence: 99%